Clinical Response to Venetoclax and Decitabine in Acute Promyelocytic Leukemia With a Novel RARA-THRAP3 Fusion: A Case Report - Song, Baoquan; Wang, Xin; Kong, Xin; Wang, Man; Yao, Li; Shen, Hongjie; Zhang, Jian; Qiu, Huiying (Frontiers in Oncology, 2022)
Variant APL showed quite different aspects, and the current treatments remained challenged at present. Venetoclax, a selective inhibitor of BCL2, is a small molecule that has been studied in several hematologic malignancies as both monotherapy and in combination with other agents. However, there are little of its use in the treatment of acute promyelocytic leukemia or variant APL. In this report, we identified THRAP3 as novel RARA fusion in resembling APL, was resistant to all-trans retinoic acid (ATRA) combined arsenic trioxide chemotherapy. Then the patient was salvaged by low dose venetoclax and decitabine. The treatment in this case demonstrates the potential ability of venetoclax in variant APL, thus providing a new treatment option for all kinds of APL.